La literatura farmacéutica Siríaca y Árabe : comparación de las recetas de El Libro de las Medicinas (siríaco) con recetas en la literatura farmacéutica árabe - Asade, Daniel J. (2017)
This doctorate thesis titled "Syriac and Arabic pharmaceutical literature. Comparison of The Book of Medicines (Syriac) with recipes in Arabic pharmaceutical literature", identifies the literary existing parallels between sixteen identical or similar medicines (in their proper name, clinical indication, pharmaceutics, conservation and references mentioned) of the medieval Arabic texts, and the Syriac-Aramaic text of a medieval manuscript edited by Budge (1913), called The Book of Medicines. Investigation also goes into the origin of the classic medicine in Greek and Latin and the antique medicine of Egypt and Mesopotamia. All drugs, simple or compound, were identified by their constitutive taxonomy. Through the philological analysis of simple drugs, the loan from the Syriac to Arabic was proven in several cases, or at least its common use name previous to the Arabic-Islamic period; therefore, adding the literary parallelism previously mentioned, we were able to demonstrate that Christians of the Syriac-Aramaic tongue were, at least in the considered cases, were earlier translators of classic medicine than the Arabic-Muslims, as indicated by academics in Syriac, Byzantine and Arab Studies, as well as specialists in History of Science.